2017
DOI: 10.1097/cej.0000000000000234
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive factors are associated with oesophageal cancer risk: results from a meta-analysis of observational studies

Abstract: To further evaluate the association between reproductive events and the development of oesophageal cancer, we searched relevant studies using electronic databases (PubMed, ISI Web of Science). Study-specific relative risks with corresponding 95% confidence intervals (CI) in all analyses were used and multiple summary relative risk (SRR) estimates were calculated. We carried out subgroup analyses and used meta-regression techniques to explore potential sources of heterogeneity. Sensitivity analysis was carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…In total, we identified 10,550 records, scrutinized 160 full-text articles, and ultimately included 60 articles (29 systematic reviews of RCTs [ 25 , 26 , 30 , 57 82 ], 27 of observational studies [ 27 , 28 , 83 107 ], and 4 of both RCTs and observational studies [ 108 111 ]) ( Fig 1 ). The studies were published between 1995 and 2017.…”
Section: Resultsmentioning
confidence: 99%
“…In total, we identified 10,550 records, scrutinized 160 full-text articles, and ultimately included 60 articles (29 systematic reviews of RCTs [ 25 , 26 , 30 , 57 82 ], 27 of observational studies [ 27 , 28 , 83 107 ], and 4 of both RCTs and observational studies [ 108 111 ]) ( Fig 1 ). The studies were published between 1995 and 2017.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, in the development of EAC only breastfeeding has been shown to be associated with a decreased risk of EAC in a study of pooled data from several case–control studies 40 . Two separate meta-analysis 41 , 42 confirmed this finding and suggested that HRT is protective whereas early menopause is a risk factor in the development of esophageal cancer. Further research is needed to provide the answer to the role of androgens and anti-androgens in the etiology of these tumors.…”
Section: Discussionmentioning
confidence: 80%
“…But some limitations should be mentioned in interpreting our findings. Firstly, studies 30,31 have shown that postmenopausal women have a higher risk of esophageal cancer than premenopausal and perimenopausal women. So, age-specific incidence and mortality in postmenopausal women should be taken into consideration in our study.…”
Section: Discussionmentioning
confidence: 99%